"So fat-lah" 30 perfect ways to a slimmer you - Tunku Halim 1964- (MPH Publishing, 2016)
'20 Secrets to a Flat Stomach?', 'The 5 Foods to Never Eat?' Those won't help you. But these 30 Perfect Ways will. Losing weight can be tough, especially for Malaysians, surrounded as they are with delicious food. This comprehensive, sometimes light-hearted but serious book gives you the clarity and knowledge to take the kilos off. It cuts through the clutter of dieting information and misinformation and explains in simple terms the relevant science and nutrition behind weight loss.